Internet Marketing: A Special Website for Visually Impaired Customers - Wan Marzuki, Wan Mardhiahani (Universiti Teknologi Petronas, 2011)
This project ,covers three aspects which are internet marketing and website accessibility and visually impaired people. The main focuses are on the implementation of the web accessibiiity in the design of the website that can be accessible to all customers either normal or visually impaired. The problems that had been found are the failure of in designing the website where as neglecting the visually impaired customers and also the challenge in convert visitor into buyer during the initial visit to website.in this project it will focus on the qualitative research to do the data collection for the purposes of the project. The data collection will be on the primary and secondary whereby the primary data gathered from the interviews that conducted and listening to web seminar meanwhile the secondary data gathered from the online journals, articles and books. The data that had been collected will be analyzed and interprc1cd in order to get the result. From the result, it can develop the design of the website and have user acceptance testing whether it is accessible for visually impaired to access the website.